ANALISIS KESULITAN SISWA SMP DALAM MENYELESAIKAN SOAL BANGUN RUANG SISI DATAR - Try Suprayo; Sugiman Sugiman; Emi Pujiastuti; Setiyani Setiyani; Vika Oktoviani (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The purpose of this study was to analyze the difficulties of junior high school students in solving flat sided space problems. This research is a qualitative descriptive study. The instruments in this study were mathematical problem solving questions on flat sided geometric material, and interview guidelines. The subjects of this study were 9 students of grade VIII junior high school. Sampling in this study used purposive sampling, namely by taking samples based on certain criteria. The results showed that students with low abilities had difficulty understanding questions, making plans for solving them and having difficulties implementing strategies or procedures to solve these problems. Students with moderate and high abilities have been able to carry out the problem solving process well. The results of this study provide recommendations that can be made to overcome students' difficulties in solving word problems including, training problem solving questions, developing teaching materials based on problem solving, providing scaffolding especially for students with low abilities, implementing various models and approaches based on problem solving abilities and using media learning